Interactive Effects of Public Foreign Capital Inflows and Domestic Investment on Growth in an Emerging Market: The Case of Nigeria - fredrick ikpesu; Babatunde O Oke (Universitas Syiah Kuala, 2022)
Do public capital inflows and domestic investment spur economic growth in the emerging market? To answer this question, this study investigated the effect of public capital inflows and domestic investment on growth in emerging markets and also the interactive effect of public foreign capital inflows and domestic investment growth in an emerging market, Nigeria between the period 1981 to 2017. The study used economic growth as the dependent variable, while public capital inflows (aid and foreign borrowing) and domestic investment as independent variables. In line with theories and empirical literature the following control variables (human capital, labour, inflation, and exchange) were also employed in the study. Findings from the study showed that foreign borrowing has an adverse effect on growth, whereas aid and domestic investment positively spur growth in Nigeria. The study outcome also showed that the interaction of foreign aid and domestic investment is positive and statistically significant an indication that the effect of foreign aid on growth depends on domestic investment. This, therefore, indicates a complementarity relationship between aid and domestic investment. Based on the study outcome, the government should attract more foreign aid into the country to increase the level of domestic investment and spur growth. The government needs to be cautious when using foreign borrowing to finance developmental projects. The terms and conditions including the rate of interest, principal repayment need to study carefully to avoid unnecessary burdens on the citizenry. It is also recommended that the borrowed fund should be tied to productive investment and not white elephant projects.